Implementasi Penguatan Budaya untuk Keberlanjutan Desa Wisata Pinge di Tengah Hegemoni Pariwisata: Implementation of Cultural Strengthening for the Sustainability of Pinge Village Tourism Amid Tourism Hegemony - Prasiasa, Dewa Putu Oka; Widari, Dewa Ayu Diyah Sri (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2024)
The development of sustainable tourism villages is anticipated to optimally fulfill three key indicators: cultural sustainability, environmental sustainability, and economic sustainability. However, numerous challenges persist, including the dynamics of authenticity and commodification, tourism political domination and hegemony, as well as the strengthening of traditional institutions. This research focuses on examining the implementation of cultural, environmental, and economic strengthening within the Pinge Tourism Village amidst tourism hegemony. Utilizing qualitative methods and a comprehensive literature review, the study reveals that cultural strengthening efforts include maintaining daily life traditions such as farming, traditional sewing (mejejahitan), flower picking, dance learning, and traditional hunting (metekap/nenggala) during specific seasons. Notably, no specific tour packages are designed exclusively for tourism, ensuring that traditions in Pinge continue as the primary focus, with the tourism village management involving elements from the traditional community. These actions represent efforts to preserve the authenticity of Pinge’s cultural products. The research also finds that the planning, development, and operations of the Pinge Tourism Village are driven by the local community, which prevents external hegemony. All societal levels contribute to the development of the tourism village. This study offers practical insights into cultural implementation for strengthening tourism villages and provides an academic contribution by proposing a cultural strengthening model for the sustainability of tourism villages with characteristics similar to those of Pinge. Abstrak Pengembangan desa wisata berkelanjutan diharapkan dapat memenuhi secara optimal tiga indikator utama: keberlanjutan budaya, keberlanjutan lingkungan, dan keberlanjutan ekonomi. Namun, dalam mewujudkannya, desa wisata masih menghadapi berbagai tantangan, termasuk dinamika autentisitas versus komodifikasi, dominasi politik pariwisata, hegemoni, serta perlunya penguatan kelembagaan tradisional. Fokus penelitian ini adalah mengkaji implementasi penguatan budaya, lingkungan, dan ekonomi dalam perkembangan Desa Wisata Pinge di tengah hegemoni pariwisata. Penelitian ini menggunakan metode kualitatif dan didukung oleh tinjauan pustaka. Hasil penelitian menunjukkan bahwa penguatan budaya dilakukan melalui pelaksanaan tradisi kehidupan sehari-hari masyarakat desa, seperti bertani, menjahit, memetik bunga, belajar menari, dan metekap/nenggala pada musimnya, tanpa membuat paket wisata khusus. Tradisi di Desa Adat Pinge tetap menjadi prioritas utama dengan pengelolaan yang melibatkan unsur Desa Adat Pinge. Implementasi tradisi sehari-hari sebagai produk budaya merupakan upaya menjaga keaslian produk budaya Desa Wisata Pinge. Penelitian ini juga menemukan bahwa perencanaan, pengembangan, dan operasional Desa Wisata Pinge berasal dari masyarakat setempat, sehingga tidak terdapat hegemoni dalam pengembangan. Semua lapisan masyarakat dilibatkan dalam pengembangan desa wisata. Penelitian ini memberikan kontribusi praktis terkait dengan implementasi budaya dalam rangka penguatan eksistensi desa wisata dan kontribusi akademis berupa model penguatan budaya yang dapat diterapkan pada desa wisata lain yang memiliki karakteristik serupa dengan Desa Wisata Pinge untuk menjaga keberlanjutan budaya.